Analysis of the Relationships between Mean Red Blood Cell Vol-ume, Red Blood Cell Distribution Width and Hypotension in Patients with Hemodialysis - Jiayong Xie; Qiang Zhu; Yuqi Qian; Gang Yao; Ying Yuan (Tehran University of Medical Sciences, 2021)
Background: We aimed to explore and analyze the relationships between mean corpuscular volume (MCV), red blood cell distribution width (RDW) and hypotension in patients with hemodialysis. Methods: The clinical data of 163 patients from the Xinghua People's Hospital, Taizhou, China with hemodialysis were retrospectively analyzed. The incidence of hypotension was counted and the levels of MCV and RDW were compared between the patients with and without hemodialysis. MCV and RDW were analyzed as possible influencing factors of hypotension. Receiver operating characteristic curve (ROC) was drawn to analyze the effect of MCV and RDW on the risk assessment of hypotension in patients with hemodialysis. Results: MCV in patients with hypotension was significantly lower than those without hypotension (P < 0.05), and RDW was higher than those without hypotension (P < 0.05). The constituent ratio of higher age (>60), diabetic nephropathy, maintenance hemodialysis, MCV < 80fl, RDW > 14.8%, malnutrition, anemia, ultra-filtration rate, diet during dialysis, coronary heart disease, atrial fibrillation and antihypertensive drugs before dialysis were higher in patients with hypotension than those without hypotension (P < 0.05). The sensitivity, specificity and AUC of the combination of MCV and RDW were higher than those of the single assessment. MCV is lower in patients with hypotension and RDW is higher than those in patients without hypotension. Conclusion: MCV combined with RDW has a good evaluation effect.